An integrated modeling framework for active traffic management and its applications in the Washington, DC area - Xiong, Chenfeng; Yang, Xianfeng Terry; Zhang, Lei; Lee, Minha; Zhou, Weiyi; Raqib, Mohammed (Journal of intelligent transportation systems, 2021)
Developing appropriate modeling and simulation tools with the capability of analyzing traffic patterns, travel demand, and traveling/driving behavior responses at the regional level is important for the evaluation of active traffic management (ATM) and real-time transportation systems management and operations (TSM&O). In this paper, an integrated travel behavior and dynamic traffic assignment modeling tool, AgBM-DTALite, has been developed and adapted for real-time and dynamic analysis of ATM and TSM&O. The ATM algorithms are tightly integrated into the system, revising the control rates on a minute-by-minute basis. This tool also successfully incorporates travel demand and behavioral sensitivity into the traffic control and operations. The model is applied in a large-scale network to evaluate several ATM strategies, including variable speed limit (VSL) and ramp metering in the Washington, DC area. Significant departure time behavioral changes are found in response to ATM and the subsequent changes in traffic conditions. The impact on traffic dynamics is also quantified using various performance metrics.